Florida Renter's Guide to Foreclosure - Michael S. Gutter; Brent Litchfield (EDIS, 2009)
FCS3306, a 2-page fact sheet by Michael S. Gutter and Brent Litchfield, describes for renters the protections provided in the federal Protecting Tenants at Foreclosure Act of 2009, and how to interact with the previous landlord so as to minimize the potential hazards of this disruptive process. Includes references. Published by the UF Department of Family Youth and Community Sciences, October 2009.